2024
DOI: 10.3390/biomedicines12040882
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Sulfhydryl (Thiols) Groups in Oral and Periodontal Diseases

Sabetim Cerkezi,
Marija Nakova,
Icko Gorgoski
et al.

Abstract: Aim. The sulfhydryl (thiols) group of glutathione plays an important role in the neutralization of foreign organic compounds and the reduction in peroxides. The purpose of the study is to evaluate the concentration of sulfhydryl groups in the gingival tissue of healthy individuals and those with gingivitis or periodontitis, and to examine the differences between these groups. Material and methods. To assess the concentration of sulfhydryl groups (thiols) in the gingival tissue of healthy individuals and those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 161 publications
0
1
0
Order By: Relevance
“…Second, studies have shown a significant correlation between the severity of periodontitis and serum levels of disulfides, which are significantly elevated in patients with periodontitis compared to the healthy population ( Tayman et al, 2021 ). Another study also confirmed that thiols with reducing properties were significantly reduced in gingival tissues of periodontitis patients ( Cerkezi et al, 2024 ), and that this reducing compound plays a crucial role in resistance to oxidative stress. Furthermore, disulfidptosis has been progressively studied in inflammatory diseases such as obligatory myelitis and ulcerative colitis ( Li et al, 2024 ; Xiong et al, 2024 ).…”
Section: Introductionmentioning
confidence: 63%
“…Second, studies have shown a significant correlation between the severity of periodontitis and serum levels of disulfides, which are significantly elevated in patients with periodontitis compared to the healthy population ( Tayman et al, 2021 ). Another study also confirmed that thiols with reducing properties were significantly reduced in gingival tissues of periodontitis patients ( Cerkezi et al, 2024 ), and that this reducing compound plays a crucial role in resistance to oxidative stress. Furthermore, disulfidptosis has been progressively studied in inflammatory diseases such as obligatory myelitis and ulcerative colitis ( Li et al, 2024 ; Xiong et al, 2024 ).…”
Section: Introductionmentioning
confidence: 63%